Comparative macro- and micromorphology of the human and rodent mandible - Paltov , Ye.V.; Dragun , A.I.; Chelpanova , I.V. (Морфологія / Morphologia / Morfologìâ, 2025)
Background. Experimental research is an integral part of modern medicine. It allows for in-depth and phased study of processes developing in the organism under specific conditions or under the influence of certain factors, both external and internal, revealing cause-and-effect relationships for further search of methods for early diagnosis of pathological changes, and development of preventive and therapeutic measures. Animal testing is justified by their significant biological similarity to humans, especially in mammals with a high degree of genetic relatedness, making them effective models for researching human diseases and developing treatments. Numerous medical studies have an experimental component and experimental animals are the primary subjects of such research. Therefore, comparative analysis of the morphogenesis of tissues, organs, and systems of the human organism and various animal species, identifying similar and different structural features, is of great importance. It should be noted that experimental animals are frequently used in studies of the structures of the oral and nasal cavities, the orbit, and individual bones of the skull. For a dentists, the jaws are of greatest interest. The aim of our research was to elucidate the species-specific features of the structure of the human mandible and those of rodents used in experimental studies, and also to evaluate the available bone volume in different areas of the mandible. Methods. 5 human mandibles and 10 rodent mandibles (rabbits and rats) were examined using macro- and microscopic, morphometric and radiographic methods, as well as atomic absorption spectral analysis. This allowed for a comparison of the structural features of the human, rabbit, and rat mandibles. Histological preparations were obtained from the archives of the histology department. Radiographic examination was performed using a Siemens dental radiovisiography apparatus with Trophy Radiology Software. Results and conclusion. In rodents, the mandible consists of two bones joined at an angle of 30-45°. The rabbit mandible has a V-shaped structure; the oral cavity is relatively deep, but the mouth does not open widely. This hinders access to the dentition, making tooth extraction and intraoral administration of mandibular nerve anesthesia impossible. There is a toothless space 18-19 mm long between the incisors and the large molars; the mental foramen is located slightly posterior to its midpoint; and there is no mental protuberance. Rabbits have four incisors on the upper jaw, primary and secondary, the latter hidden behind the primary ones. The lower jaw, like that of the rat, has only two incisors. The height of the interdental region of the alveolar part of the mandible is 0.6 to 1.3 cm, significantly different from that in rats. Radiographically, the roots of the incisors lie within the bone tissue of the body of the mandible up to the retromolar space. The roots of the large molars are short and lie within the bone tissue of the alveolar part of the mandible. The height and length of the molar localization area of the mandible are practically the same – 1.5 x 1.5 cm. We observed particularly well-developed compact bone in the lower border of the body in the area of its angles and rami, articular processes, and in the areas of muscle attachment. Thinner compact plates are located in the area of the tooth sockets. The cancellous bone of humans, rabbits, and rats forms cells of varying shape and size, filled with bone marrow. Often, expanded intertrabecular spaces contain adipose tissue, as seen in the presented preparations. Rodents are distinguished by the presence of a large number of adipocytes in the intertrabecular spaces, while in humans, the spaces of the cancellous bone tissue are filled with hematopoietic cells. Despite the differences in the macromorphology of the human and rodent mandibles, the histoarchitecture of the bone tissue of the latter can be considered similar. This indicates the possibility of using this group of animals as experimental subjects in studies of the structural and functional characteristics of bone tissue and their dynamics under the influence of various pathological factors.